Deciphering the consecutive electronic modulation and interfacial water activation of cobalt-incorporated tungsten diselenide electrocatalysts - Nasrin Banu G; Rama Prakash M; Ramesh Poonchi Sivasankaran; Muthupandi Senthilkumar; Wonyong Choi; Young Soo Kang; Bernaurdshaw Neppolian (Chemical Engineering Journal, 2026)

A Walking Type Self-Propelled Single-Row Carrot Harvester-Cum-Detopper for Hilly Region - T. Senthilkumar; S. Syed Imran; G. Manikandan; R. Sanjay Krishnan (Agricultural Research, 2026)

Aflatoxin detection and quality assessment in dried red chilli (Capsicum annum L.): A multifaceted approach using physical, microstructural, and machine learning techniques - M. Balasubramaniyan; J. Shavani Durga; V. Chelladurai; T. Senthilkumar; T. Krishnakumar; G. Jeevarathinam (Journal of Stored Products Research, 2026)

An extensive evaluation framework employing analytical, numerical, and probabilistic methods to assess irregularity in RC buildings on hill slopes during earthquakes - Babaji Patil; Ananda Mitra; L. Aditya; G. Tamizharasi; R. Senthilkumar (Soil Dynamics and Earthquake Engineering, 2026)

Mitigating pounding through drift limitations: a focus on buildings with re-entrant corner - Ananda Mitra; Shailesh Lahoti; A. Laghate; G. Tamizharasi; R. Senthilkumar (Innovative Infrastructure Solutions, 2025)

Integrated deterministic and probabilistic assessment of reinforced concrete buildings featuring transfer structures under earthquake shaking - Vikrant Parthe; L. Aditya; Ananda Mitra; G. Tamizharasi; R. Senthilkumar (Bulletin of Earthquake Engineering, 2025)

Retraction notice to “Investigation of pure and g-C3N4 loaded CdWO4 photocatalytic activity on reducing toxic pollutants” [Chemosphere 291, Part 3, March 2022, 133090] - S.P. Keerthana; R. Yuvakkumar; P. SenthilKumar; G. Ravi; S.I. Hong; Dhayalan Velauthapillai (Chemosphere, 2025)

Unraveling the genetic potential of wild rice (Oryza rufipogon) for sustainable food security - Himaswetha Rajan; K. N. Ganesan; S. Manonmani; C. Gopalakrishnan; G. Senthilkumar; R. Suresh (Genetic Resources and Crop Evolution, 2025)

Genotype × Environment Interaction Analysis and Simultaneous Selection Using AMMI, BLUP, GGE Biplot and MTSI Under Drought Condition in Sweet Potato - K. H. Gowda; V. B. S. Chauhan; M. Nedunchezhiyan; C. Pradeepika; K. M. Senthilkumar; V. Chandra; G. Byju; M. R. Sahoo; K. Pati; R. Arutselvan (Journal of Soil Science and Plant Nutrition, 2025)

K-means Pelican Optimization Algorithm based Search Space Reduction for Remote Sensing Image Retrieval - W. T. Chembian; G. Senthilkumar; A. Prasanth; R. Subash (Journal of the Indian Society of Remote Sensing, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

High Xylanase and Low Cellulase Producing Bacteria as a Whole Cell Biocatalyst for Eco-Friendly Surface Modification of Banana Pseudostem Fibers - Ajinath Dukare; Krishna Prasad; G. T. Senthilkumar; Kirti Jalgaonkar; Sujata Saxena (BioEnergy Research, 2024)

Augmentin loaded functionalized halloysite nanotubes: A sustainable emerging nanocarriers for biomedical applications - Deepak Verma; Manunya Okhawilai; Nangan Senthilkumar; Karthik Subramani; Aran Incharoensakdi; G. Ganesh Raja; Hiroshi Uyama (Environmental Research, 2024)

BIN1 in the Pursuit of Ousting the Alzheimer’s Reign: Impact on Amyloid and Tau Neuropathology - Ishnoor Kaur; Tapan Behl; G. Sundararajan; P. Panneerselvam; A. R. Vijayakumar; G. P. Senthilkumar; T. Venkatachalam; Dharmender Jaglan; Shivam Yadav; Khalid Anwer; Neeraj Kumar Fuloria; Aayush Sehgal; et al. (Neurotoxicity Research, 2023)

Assessment of solar thermal monitoring of heat pump by using zeolite, silica gel, and alumina nanofluid - G. Antony Casmir Jayaseelan; A. Surenderpaul; T. Thandial Selvam; A. Anderson; A. Senthilkumar; Avinash Malladi; R. Venkatesh; V. N. Aneesh; R. Saravanan (Clean Technologies and Environmental Policy, 2023)

Halotolerant Nodule Rhizobial and Passenger Endophytes Alleviates Salinity Stress in Groundnut (Arachis hypogaea L.) - G. Oviya; Anandham Rangasamy; Manikandan Ariyan; R. Krishnamoorthy; M. Senthilkumar; N. O. Gopal; S. Thiyageshwari; S. Meena; S. Vincent (Journal of Plant Growth Regulation, 2023)

Implementation of Micro-Nanobubbles Technology for the Treatment of Domestic Wastewater: Experimental Study - G. Senthilkumar; S. Lakshmi Sankar (Water, Air, & Soil Pollution, 2023)

Isolation and genetic analysis of Porcine circovirus 2 in southern India evidences high circulation of Porcine circovirus 2d genotype - S. Parthiban; A. Ramesh; Anbu Kumar Karuppannan; G. Dhinakar Raj; S. Hemalatha; M. Parthiban; K. Senthilkumar; D. Balasubramaniyam; R. Sumanth Kumar; S. Ranganatha; Chintu Ravishankar (Molecular Biology Reports, 2022)

Molecular evidence of porcine circovirus 3 infection in swine: first report in southern India - S. Parthiban; A. Ramesh; G. Dhinakar Raj; Anbu Kumar Karuppannan; S. Hemalatha; M. Parthiban; Chintu Ravishankar; K. Senthilkumar; D. Balasubramaniyam (VirusDisease, 2022)

Reuse of Uncontrolled Burnt Bagasse Ash from Sugar Industries with Waste Rubber Powder in Construction: A Waste to Wealth Approach for Sugar Mills - K. S. Teja; R. Senthilkumar; G. Athira; A. Bahurudeen (Sugar Tech, 2022)

Molecular detection of porcine parvovirus 1–associated reproductive failure in southern India - S. Parthiban; R. K. V. Sowndhraya; P. Raja; M. Parthiban; A. Ramesh; G. Dhinakar Raj; K. Senthilkumar; D. Balasubramanyam; S. Hemalatha; R. Bharathi; Chintu Ravishankar; S. Thahira Parveen (Tropical Animal Health and Production, 2022)

Distribution and toxicity of Bacillus thuringiensis (Berliner) strains from different crop rhizosphere in Indo-Gangetic plains against polyphagous lepidopteran pests - G. K. Sujayanand; Mohd Akram; Aravind Konda; Ashish Nigam; Shripad Bhat; Jyotirmay Dubey; Krishna Kumar; Senthilkumar K. Muthusamy (International Journal of Tropical Insect Science, 2021)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Diagnosis of Mycobacterium bovis in Captive Sloth Bears (Melursus ursinus) by Polymerase Chain reaction - M. Veeraselvam; R. Sridhar; T. M. A. Senthilkumar; P. Perumal; M. G. Jayathangaraj (Proceedings of the Zoological Society, 2015)

Are mini DNA-barcodes sufficiently informative to resolve species identities? An in silico analysis using Phyllanthus - R. SRIRAMA; B. R. GURUMURTHY; U. SENTHILKUMAR; G. RAVIKANTH; R. UMA SHAANKER; M. B. SHIVANNA (Journal of Genetics, 2014)

Viral and bacterial aetiologies of epithelial ovarian cancer - S. Shanmughapriya; G. SenthilKumar; K. Vinodhini; B. C. Das; N. Vasanthi; K. Natarajaseenivasan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

In vitro cytotoxicity and induction of apoptosis by ruthenium(II) complexes in HL-60 and K-562 - S. Bhattacharya; Subhas S. Karki; R. Suresh; L. Manikandan; G. P. Senthilkumar; M. Gupta; Upal K. Mazumder; R. Balaji; K. Murali (Medicinal Chemistry Research, 2012)

Influence of hydraulic retention time in a two-phase upflow anaerobic sludge blanket reactor treating textile dyeing effluent using sago effluent as the co-substrate - M. SenthilKumar; G. Gnanapragasam; V. Arutchelvan; S. Nagarajan (Environmental Science and Pollution Research, 2011)

Recycle in upflow anaerobic sludge blanket reactor on treatment of real textile dye effluent - G. Gnanapragasam; M. Senthilkumar; V. Arutchelvan; P. Sivarajan; S. Nagarajan (World Journal of Microbiology and Biotechnology, 2010)

Delineation of potential zones for artificial recharge using gis - V Jothiprakash; G Marimuthu; R Muralidharan; N Senthilkumar (Journal of the Indian Society of Remote Sensing, 2003)

Isolation, PCR based identification, and sensitivity pattern of environmental mycobacteria from leprosy and tuberculosis patients - D. Saravanakumar; N. Elangeswaran; S. Senthilkumar; G. Vanaja; S. Kamakshiammal; C. Chandrasekar; C. N. Deivanayagam; Manjula Sritharan; V. Sritharan (Indian Journal of Clinical Biochemistry, 2000)